The Cannabinoid Receptor 1 Reverse Agonist AM251 Ameliorates Radiation-Induced Cognitive Decrements - Parihar, Vipan K.; Syage, Amber; Flores, Lidia; Lilagan, Angelica; Allen, Barrett D.; Angulo, Maria C.; Song, Joseph; Smith, Sarah M.; Arechavala, Rebecca J.; Giedzinski, Erich; Limoli, Charles L. (Frontiers in Cellular Neuroscience, 2021)
Despite advancements in the radiotherapeutic management of brain malignancies, resultant sequelae include persistent cognitive dysfunction in the majority of survivors. Defining the precise causes of normal tissue toxicity has proven challenging, but the use of preclinical rodent models has suggested that reductions in neurogenesis and microvascular integrity, impaired synaptic plasticity, increased inflammation, and alterations in neuronal structure are contributory if not causal. As such, strategies to reverse these persistent radiotherapy-induced neurological disorders represent an unmet medical need. AM251, a cannabinoid receptor-1 reverse agonist known to facilitate adult neurogenesis and synaptic plasticity, may help to ameliorate radiation-induced CNS impairments. To test this hypothesis, three treatment paradigms were used to evaluate the efficacy of AM251 to ameliorate radiation-induced learning and memory deficits along with disruptions in mood at 4- and 12-weeks post-irradiation. Results demonstrated that acute (4 weekly injections) and chronic (16 weekly injections) AM251 treatments (1 mg/kg) effectively alleviated cognitive and mood dysfunction in cranially irradiated mice. The beneficial effects of AM251 were exemplified by improved hippocampal- and cortical-dependent memory function on the novel object recognition and object in place tasks, while similar benefits on mood were shown by reductions in depressive- and anxiety-like behaviors on the forced swim test and elevated plus maze. The foregoing neurocognitive benefits were associated with significant increases in newly born (doublecortin+) neurons (1.7-fold), hippocampal neurogenesis (BrdU+/NeuN+ mature neurons, 2.5-fold), and reduced expression of the inflammatory mediator HMGB (1.2-fold) in the hippocampus of irradiated mice. Collectively, these findings indicate that AM251 ameliorates the effects of clinically relevant cranial irradiation where overall neurological benefits in memory and mood coincided with increased hippocampal cell proliferation, neurogenesis and reduced expression of proinflammatory markers.